Protein therapeutics - Vaughan, Tristan; Osbourn, Jane; Jallal, Bahija (Weinheim, Germany : Wiley-VCH, 2017)
In this practice-oriented two volume handbook, professionals from some of the largest biopharmaceutical companies and top academic researchers address the key concepts and challenges in the development of protein pharmaceuticals for medicinal chemists and drug developers of all trades. Following an introduction tracing the rapid development of the protein therapeutics market over the last decade, all currently used therapeutic protein scaffolds are surveyed, from human and non-human antibodies to antibody mimetics, bispecific antibodies and antibody-drug conjugates. This ready reference then goes on to review other key aspects such as pharmacokinetics, safety and immunogenicity, manufacture, formulation and delivery. The handbook then takes a look at current key clinical applications for protein therapeutics, from respiratory and inflammation to oncology and immune-oncology, infectious diseases and rescue therapy. Finally, several exciting prospects for the future of protein therapeutics are highlighted and discussed.
2.5 Evolution of Concepts in Antibody Pharmacology 2.5.1 Neutralization ; 2.5.2 From Killing Bacteria to Killing Human Cells ; 2.5.3 Targeting Membrane Receptors ; 2.6 Future Directions for Antibody Therapeutics Development ; Acknowledgments ; References
Includes bibliographical references and index.
Keywords: Protein drugs; Proteins -- Therapeutic use; MEDICAL / Pharmacology; Protein drugs; Proteins -- Therapeutic use; Electronic books; Electronic books